2013
DOI: 10.1021/ef400511s
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Different Recovery Methods for Orinoco Belt Heavy Oil after Solution Gas Drive

Abstract: Although foamy oil can improve the performance of solution gas drive in heavy oil, only about 5–15% original oil in place (OOIP) can be recovered under primary production. In this study, a series of micromodel flood experiments and sandpack flood tests were performed to evaluate the performances of water flooding, surfactant flooding, gas flooding, and foam flooding for enhancing the recovery of Orinoco Belt heavy oil after solution gas drive. Water flooding tests show that the sweep efficiency of water floodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…For the SiO 2 /SDS foam, the foam had lateral pressure on the pore wall, so the residual was extruded and pulled out. Lu et al 41 found that it was mainly because of the viscoelasticity of bubbles. Bubbles kept their spherical shape due to the adsorption of SiO 2 and deformed when they were in contact with the oil droplet.…”
Section: Displacement Of Sds Foammentioning
confidence: 99%
“…For the SiO 2 /SDS foam, the foam had lateral pressure on the pore wall, so the residual was extruded and pulled out. Lu et al 41 found that it was mainly because of the viscoelasticity of bubbles. Bubbles kept their spherical shape due to the adsorption of SiO 2 and deformed when they were in contact with the oil droplet.…”
Section: Displacement Of Sds Foammentioning
confidence: 99%
“…In this study, it can be seen that foamy oil is also an important mechanism to improve the performance of CO 2 huff and puff. Because foamy oil can reduce the mobility of gas and provide tremendous energy to the system, the depletion rate of pressure in the micromodel for Run a was lower than Run b, as shown in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…Most researchers agree that foamy oil is the primary mechanism of the solution gas drive process in heavy oil . In foamy oil, gas is dispersed in high concentrations in the oil as small gas bubbles; however, although foamy oil can improve the performance of solution gas drives in heavy oil, only 5‒15% of the original oil in place (OOIP) can be recovered via a solution gas drive …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the artificial core flooding apparatus and other apparatus used in this experiments can be found elsewhere[39]. The schematic of the microscopic drilling fluid displacement experimental apparatus is shown inFigure 3.…”
mentioning
confidence: 99%